Followership in business transformation: Hyundai Motor group case - Kyounghee Sunwoo; Jinhee Choi; Victor Blazquez (Administrative Sciences, 2024)
This study explored the employees' perception of followership and its evolution in business transformation, given the case of the Hyundai Motor Group (HMG). Using a case study approach for explorative research, we conducted informal conversations and in-depth interviews with twenty participants to solicit employees' and stakeholders' perceptions of followership and its cultural formation through interpersonal relationships. Drawing on Kelley's followership typology, we found three characteristics in participants' followership perceptions: Ill-sa-bul-lan (extraordinarily well-organized), speed, and devotion. To explore the cultural formation of followership between leaders and followers, which is under-explored in Kelley's theory, we adopted alternative theories (i.e., responsible leadership and implicit followership) to analyze the interpersonal relationship during the business transformation. Consequently, we found that the HMG followership, shaped by the relationships between leaders and followers within the Korean cultural context, evolved to facilitate successful business transformation. Initiated by top management, new and diverse elements from outside spurred the drive for business transformation and instigated changes in organizational culture, including perceptions of followership. This evolution of followership, in turn, reinforced the business transformation, creating a virtuous cycle. This study offers valuable insights into the dynamics of followership and its impact on organizational performance, providing a foundation for further empirical research in this underexplored area of followership.
Keywords: 350; Hyundai Motor Group (HMG); followership; followership typology; mechanism; businesstransformation; Korean culture